Suckling productivity of cows of Ukrainian red suckling breed in connection with their reproductive ability - Вацький, В. Ф.; Величко, С. А. (Scientific Progress & Innovations, 2012)
The features of connection of the suckling productivity and reproductive ability of cows of Ukrainian red suckling breed are studied. It is set that with the increase of suckling productivity level, reproductive ability of cows gets worse. It is defined, that an optimal service-period is within 51-90 days; for highly productive cows duration of service period to 121 day is not a critical. An index which characterized the level of cows suckling productivity in taking into account their reproductive ability is offered. The results of researches enable to improve the use of suckling cattle in an economy by correct organization of herd reproduction.